2022
DOI: 10.1108/jocm-07-2021-0201
|View full text |Cite
|
Sign up to set email alerts
|

The impact of leadership on perceived work-related stress in healthcare facilities organisations

Abstract: PurposeEmployees in the private, public, and third sectors have experienced an increase in stress over the years. Amongst the sectors, people working in hospitals and other healthcare facilities were put under severe stress during the COVID-19 pandemic. Indeed, the World Health Organisation has clearly stated that defending people's mental health at this particular time of restless pandemic growth is an absolute necessity. The purpose of this article is to assess the perceived work-related stress (WRS) of heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Previous studies show that supportive management led to a decreased risk of mental health problems among healthcare professionals working during the COVID-19 pandemic [ 42 – 44 ]. Also, studies show that burnout among doctors can be prevented if management facilitates a reduced workload with sufficient time for recovery [ 24 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies show that supportive management led to a decreased risk of mental health problems among healthcare professionals working during the COVID-19 pandemic [ 42 – 44 ]. Also, studies show that burnout among doctors can be prevented if management facilitates a reduced workload with sufficient time for recovery [ 24 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…A lower level of social support from management regarding the extent of the measures taken to protect the health of healthcare professionals was associated with mental health problems during the pandemic [ 41 ]. On the other hand, more supportive management, for instance through encouragement and provision of sufficient resources, helped to reduce work-related stress among healthcare professionals who worked during the COVID-19 pandemic [ 42 ]. Similarly, Feingold et al [ 43 ] showed that feeling valued and supported by management was associated with a lower risk of mental health problems during the pandemic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Today, Stress Is a Problem That Needs to be Overcome (35). Therefore, Stress Has Been Associated With Many Variables (24,(36)(37)(38)…”
Section: Perceived Stress and Emotional Intelligencementioning
confidence: 99%
“…To better understand and manage the stress, many models relating to stress have been created. The WRS model defines stress as all responses that cause any modification of an individual's cognitive, physical, psychological, and emotional state (5) . Due to differences in biological and psychosocial processes, females are more disadvantaged and vulnerable than males when it comes to the impacts of stress (6) .…”
Section: Introductionmentioning
confidence: 99%